REGULATION AND SUPERVISION OF ISLAMIC BANKING IN INDONESIA: AN IN-DEPTH EXAMINATION OF RECENT DEVELOPMENTS ANDCONTEMPORARY TRENDS - Shohib Muslim; Gunawan Widjaja; Farika Nikmah; Muhammad Naufal Arifiyanto; Mohammad Ahmad Bani Amer (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This paper conducts an in-depth examination of the regulation and supervision of Islamic banking in Indonesia, focusing on recent developments and contemporary trends. The regulatory framework governing Islamic banking has evolved significantly in response to the dynamic financial landscape and the growing prominence of Sharia-compliant finance. The study explores the historical development of regulations, vital legal provisions, and the role of regulatory authorities in overseeing Islamic banking activities. A comparative analysis with conventional banking regulations provides insights into the distinctive features and challenges the Islamic banking sector faces. The discussion delves into the effectiveness of existing regulations in addressing challenges, ensuring compliance, and facilitating enforcement. Furthermore, the study investigates evolving trends, including recent developments within the Indonesian Islamic banking sector and global perspectives on Islamic banking regulation. The implications for future research and practical recommendations are also discussed, contributing to the ongoing dialogue on strengthening the regulatory environment for Islamic banking in Indonesia.